Sticky bacteria: Combined effect of galactose and high ferric iron concentration on extracellular polymeric substances production and the attachment of Acidithiobacillus ferrooxidans on a polymetallic sulfide ore surface - Moncayo, Eduardo A.; Debut, Alexis; Vizuete, Karla; Jumbo-Flores, Diana; Aguirre, Paulina (Frontiers in Microbiology, 2022)
Adaptation and microbial attachment mechanisms for the degradation of sulfide ores are mediated by the production of extracellular polymeric substances (EPS) and their role in biofilm formation. EPS production responds to induction mechanisms associated with environmental conditions. In this study, the double induction of EPS with galactose and high ferric iron concentrations in planktonic cells of A. ferrooxidans and their attachment on the surface of a polymetallic sulfide ore from Bella Rica-Azuay in Ecuador were evaluated. A. ferrooxidans cells were previously adapted to different concentrations of galactose (0%, 0.15% and 0.25% (w/v)) using two ferrous iron concentrations as energy source (9 g·L-1and 18gL-1) in 9K culture medium. EPS production and its effect on mineral attachment were determined at the time point of maximal growth. The results obtained show a maximum cell attachment of 94.1% within 2 hours at 0.15% of galactose and 18 g·L-1 of ferric iron concentration compared to 71.4% without galactose and 9 g·L-1 of ferric iron. The maximum concentration of EPS was obtained with 0.25% galactose concentration; however, it did not result in greater attachment compared to 0.15% galactose concentration. Through the combined induction of low galactose concentration and high ferric iron concentration, the percentage of bacterial attachment can be increased and, therefore, a possible increase in the rate of biooxidation and bioleaching could be obtained.